Variations in survival and perioperative complications between hospitals based on data from two phase III clinical trials for oesophageal cancer. Issue 9 (11th June 2015) - Kataoka, K.; Nakamura, K.; Mizusawa, J.; Fukuda, H.; Igaki, H.; Ozawa, S.; Hayashi, K.; Kato, K.; Kitagawa, Y.; Ando, N.
<x xml:space="preserve">Abstract</x> Background Variations in institutional practice may contribute to different outcomes of cancer treatment. The impact of interinstitutional heterogeneity on outcomes between hospitals after oesophagectomy has not been examined previously using data from surgical clinical trials. Methods The data from two phase III trials for oesophageal cancer were used. Japan Clinical Oncology Group (JCOG) 9204 involved oesophagectomy (92‐OP) versus oesophagectomy plus postoperative chemotherapy (92‐POST), with accrual from 1992 to 1997. JCOG9907 involved postoperative chemotherapy (99‐POST) versus preoperative chemotherapy (99‐PRE), with accrual from 2000 to 2006. Hospitals contributing fewer than three patients were excluded. The influence of time and preoperative chemotherapy on interinstitutional heterogeneity related to postoperative complications and 5‐year overall survival were evaluated by comparisons within and between these trial groups. Heterogeneity was estimated by a mixed‐effects model after adjusting for age, sex, performance status, location of the primary tumour and clinical stage. Results Twelve hospitals in 92‐OP (114 patients), 13 in 92‐POST (114), 19 in 99‐POST (158) and 18 in 99‐PRE (154) were eligible. There was considerable heterogeneity in predicted postoperative complications in both groups in JCOG9204 (median 31·3 (range 15·0–68·2) per cent), and in 99‐PRE (35·2 (22·6–46·6) per cent) but not in 99‐POST (27·7 (27·7–27·7) per cent) from JCOG9907. A similar pattern was seen for predicted overall survival (92‐POST: 66·4 (range 64·1–68·9) per cent; 99‐PRE: 55·9 (54·0–59·7) per cent; 99‐POST: 44·4 (44·4–44·4) per cent). Conclusion Interinstitutional heterogeneity regarding complications and survival after oesophagectomy is a problem that merits wider consideration.